Outsourcing Legal Aid in the Nordic Welfare States (Springer International Publishing, 2018)
This edited collection provides a comprehensive analysis of the differences and similarities between civil legal aid schemes in the Nordic countries whilst outlining recent legal aid transformations in their respective welfare states. Based on in-depth studies of Norway, Sweden, Finland, Denmark, and Iceland, the authors compare these cases with legal aid in Europe and the US to examine whether a single, unique Nordic model exists. Contextualizing Nordic legal aid in relation to welfare ideology and human rights, Hammerslev and Halvorsen Rønning consider whether flaws in the welfare state exist, and how legal aid affects disadvantaged citizens. Concluding that the five countries all have very different legal aid schemes, the authors explore an important general trend: welfare states increasingly outsourcing legal aid to the market and the third sector through both membership organizations and smaller voluntary organizations. A methodical and compas sionate text, this book will be of special interest to scholars and students of the criminal justice, the welfare state, and the legal aid system.